2021
DOI: 10.3390/economies9040158
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Financial Development and Energy Consumption in South Africa

Abstract: This paper examines the nexus between financial development and energy consumption in South Africa. To determine the long run and short run relationship between financial development and energy consumption in South Africa, the paper uses an Auto Regressive Distributed Lag bounds test (ARDL) and Granger causality test to establish the type of correlation between 1980 and 2018. ARDL bounds testing method offers concrete long-run estimates and t-statistics as it is flexible whether the adopted variables are I(0) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 66 publications
2
14
0
Order By: Relevance
“…A series of literature analyzed the relationship of financial development and energy consumption from the empirical perspective. Several scholars [ 9 , 10 , 11 ] discovered that financial development has a positive influence on energy consumption, and others [ 12 , 13 , 14 ] found evidence that financial development could reduce energy consumption. Besides, the empirical results of some literature indicated that the relationship between financial development and energy consumption is complex.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A series of literature analyzed the relationship of financial development and energy consumption from the empirical perspective. Several scholars [ 9 , 10 , 11 ] discovered that financial development has a positive influence on energy consumption, and others [ 12 , 13 , 14 ] found evidence that financial development could reduce energy consumption. Besides, the empirical results of some literature indicated that the relationship between financial development and energy consumption is complex.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lefatsa et al [37] concluded that various methodologies employed by researchers across different periods in both developed and developing countries, including South Africa, have yielded mixed findings regarding the relationship between renewable energy, financial development, and economic growth. Upon examining the literature, it became apparent that the conclusions reached by Lefatsa et al [37] are consistent with the findings of this study as the literature reviewed revealed that the nexus between renewable energy supply, financial development, and economic growth is inconclusive due to the findings being inconsistent, highlighting a gap that the current study aims to address.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a study by Shahbaz et al [36] on 34 developing countries, including South Africa, discovered that financial development has a long-term effect on renewable energy supply. In a South African context, Lefatsa et al [37] concluded that financial development positively impacts renewable energy consumption, and that the government should develop policies to encourage the financial sector to fund renewable energy infrastructure development projects. Inconsistent with the results of Lefatsa et al [37], Odhiambo [38] concluded that financial development did not impact renewable energy consumption in the long run in South Africa.…”
Section: Nexus Between Renewable Energy Supply and Financial Developmentmentioning
confidence: 99%
“…Efficient resource allocation in financial markets boosts growth and increases private energy consumption [ 67 , [69] , [70] , [71] ]. Although, affordable prices in the financial markets improve the purchase of consumer durables, ultimately increasing the energy demand [ 64 , 72 , 73 ].…”
Section: Relevant Literaturementioning
confidence: 99%